Mechanisms of Senescence-Related NKG2D Ligands Release and Immune Escape Induced by Chemotherapy in Neuroblastoma Cells - Zhang, Yan; Hu, Ruimin; Xi, Bixin; Nie, Dimin; Xu, Hanxiao; Liu, Aiguo (Frontiers in Cell and Developmental Biology, 2022)
The aim of this study was to investigate the mechanism of immune escape through the release of NKG2D ligand by both paracrine and exosomal pathways in chemotherapy-induced senescent neuroblastoma, which inhibits the killing function of NK cells. A senescence model was constructed using a low-dose chemotherapeutic drug doxorubicin and Aurora A inhibitor MLN8237 acting on neuroblastoma cells. ELISA was performed to detect the secretion of the NKG2D ligand MICA/B. Exosomes were extracted from the supernatant of senescent cell culture medium, and flow cytometry was used to detect the effect of exosomes on NKG2D expression in NK cells. Western blotting, qPCR and immunofluorescence were used to detect the expression of ADAM10 in senescent cells and the effect of drug inhibition of ADAM10 on MICA/B expression and release and NK cell killing function. The relationship between lncRNA MALAT1/miR-92a/ADAM10 was verified using a dual luciferase assay, and its role in NKG2D-mediated immune escape was confirmed by knocking down MALAT1 by transfection. Four different neuroblastoma cell lines showed increased secretion of the NKG2D ligand MICA/B after induced senescence. Chemotherapy-induced cell senescence stimulated the release of MICA/B-containing exosomes and inhibited the expression of NKG2D receptors in immune cells. Cellular ADAM10 expression was significantly upregulated after senescence. The combination of the ADAM10 inhibitor GI254023X with chemotherapeutic drugs inhibited the secretion of MICA/B, retained them on the cell surface, and enhanced the recognition ability of immune cells. Meanwhile, the expression of senescent cell lncRNA MALAT1 was upregulated, and MALAT1 regulated miR-92a through competitive inhibition, thus upregulating the expression of ADAM10. Intracellular transfection of siRNA to inhibit the expression of MALAT1 reversed the above phenomenon while downregulating the secretion level of MICA/B and enhancing the recognition and killing function of NK cells. This study confirms that neuroblastoma stimulated by chemotherapeutic drugs in the process of aging upregulates the expression of ADAM10 through the lncRNA MALAT1/miR-92a/ADAM10 axis and promotes the shedding of the NKG2D ligand MICA/B from tumor cells, while some MICA/B molecules can act on NK cells via exosomes, together forming a suppressive immune microenvironment and thus achieving immune escape.